INFLUENCE OF EDUCATIONAL INNOVATION ON THE DEVELOPMENT OF CREATIVE CULTURE OF FUTURE TEACHERS - Лебідь, В.П.; Пащенко, М.І.; Шарапанюк, А.Й. (SWorldJournal, 2023)
The article substantiates the essence of innovation as a separate field of scientific knowledge. The main components of educational innovation and promising directions of educational innovation are highlighted. Modern requirements for the professional tr